The SENA Memory Preservation Project, a contribution to institutional knowledge management - Gutiérrez Ortega, Martha Luz
The National Learning Service (SENA) is a national a public institution which offers free technical, technological and complementary training programs. For 60 years, it has developed a valuable bibliographical and audiovisual collection that demonstrates pedagogical experiences and good practices in the training of human resources linked to the productive sector. Thus, taking into account the impact of the institution, the SENA Library System implemented the Institutional Memory Preservation Project which, sponsored by the International Federation of Library Associations and Libraries, aims to preserve the knowledge found  in the written material and audio-visual material by retrieving and selecting materials from SENA’s physical libraries to preserve the know-how, which is constituted as the heritage of the institution, to allow open access to intellectual production through the Institutional Repository, available at http://repositorio.sena.edu.co